A preliminary studi on the morphology cultured oysters,(Crassostrea iredalei) and its parasites - Chandrika Devi Subramaniam (Terengganu: Kolej Universiti Terengganu, 2013)
The morphology and parasites of the cultured local species, Crassostrea iredalei from Setiu , Terengganu has been studied. The gross anatomy of Crassostrea iredalei showed that this species can be differentiated from the other species by the presence of the black scar of the adductor muscle. Histology was also carried out on this species.